PENGARUH CASH RATIO, RETURN ON ASSETS, GROWTH, DEBT TO EQUITY RATIO, FIRM SIZE, DAN KEPEMILIKAN INSTITUSIONAL TERHADAP DIVIDEND PAYOUT RATIO - Ahmad Afas, Suprihatmi Sri Wardiningsih & Setyaningsih Sri Utami (JURNAL EKONOMI DAN KEWIRAUSAHAAN, 2017)
Investors investing aims to earn income (dividend yield) and the differencebetween the selling price of stock over its purchase price (capital gain). Investors asshareholders expect to get large dividends, or at least relatively stable from year to year.The problem in this study is whether there is a significant influence cash ratio, ROA,growth, debt to equity ratio, firm size and the institutional ownership of the dependentvariable is the dividend payout ratio at manufacturing companies in the Indonesia StockExchange. The purpose of research is to analyze the significance of the effect of the cashratio, ROA, growth, debt to equity ratio, firm size and the institutional ownership of thedependent variable is the dividend payout ratio at manufacturing companies in theIndonesia Stock Exchange. The research method uses a case study, the type of data usedquantitative and qualitative data, the data source used secondary data. The populationin this study are all manufacturing companies listed in Indonesia Stock Exchange for theperiod 2013-2015 as many as 141 companies, the sampling technique used purposivesampling that a number of the 30 samples, the data collection methods useddocumentation. Data analysis techniques used classical assumption test, multiple linearregression analysis, t-test, F, and the coefficient of determination. In conclusion, that thecash ratio, debt to equity ratio, firm size and institutional ownership has no significanteffect on the dividend payout ratio at manufacturing companies in the Indonesia StockExchange, while the ROA and growth significantly influence the dividend payout ratio atmanufacturing companies in Indonesia Stock Exchange,Keywords: cash ratio, ROA, growth, debt to equity ratio, firm size, institutionalownership, dividend payout ratio.